Applying lean flows in pathology laboratory remodelling. Issue 2 (13th May 2014) - J. Hayes, Kathryn; Reed, Nick; Fitzgerald, Anneke; Watt, Vicki
Abstract : Purpose: – This purpose of this paper is to examine the application and outcomes of applying all of the seven lean flows to pathology laboratory remodelling as part of a lean rapid improvement event (RIE). Design/methodology/approach: – Longitudinal case study of a lean RIE linking emergency and pathology departments focusing on the systematic application of lean's seven flows to the physical environment. Findings: – Following the lean RIE, changes improving patient specimen, technician, supplies and information flows avoided 187 km and eight days of unnecessary walking each year. Research limitations/implications: – The difficulty of making accurate comparisons between time periods in a health care setting is acknowledged. Practical implications: – This research provides evidence that applying lean design concepts in a laboratory can make substantial improvements, particularly if the expertise of the people working in the laboratory is trusted to determine the most appropriate changes. Significant amounts of time and motion were saved by just one, easily quantifiable change. Social implications: – The laboratory staff is processing increased numbers of time-critical tests, yet report a calmer working environment, without any increase in the pace of work. Laboratory personnel also experienced satisfaction in exercising control over their work environment. Originality/value: – To the best of the authors' knowledge this is the first comprehensive report applying lean flows to pathology laboratory remodelling and one of the few applications of Lean Systems Thinking between departments and between separate health services organisations.